Sentinel injuries in child abuse: a multidisciplinary approach - Andrea Costantino; Giovanni Grassi; Antonio Corsello; Francesca Iasi; Giuseppe Ledda; Marco Cirillo; Emma B. Croce; Luca Saba; Simone Grassi (International Journal of Legal Medicine, 2026)
Abstract Child maltreatment represents a major public health and forensic issue, frequently underdiagnosed and associated with severe short- and long-term consequences. Sentinel injuries (SI)—minor and unexplained findings such as bruises and fractures—are often the first clinical indicators of abuse and may precede more severe events. Their early recognition is therefore crucial for prevention. This narrative multidisciplinary pictorial review uses confirmed illustrative forensic-radiological cases from the University Hospital of Cagliari to provide a multidisciplinary overview of clinical, radiological, and forensic aspects of SI. These cases are organized by anatomical districts, focusing on abusive head trauma (AHT), rib, metaphyseal fractures, and bruising patterns with higher specificity for abuse. Differential diagnoses, including bone fragility and coagulation disorders, must also be considered. Imaging, particularly skeletal surveys with follow-up, chest and cranial studies, plays a central role but is often inconsistently applied. The probabilistic nature of abuse diagnosis requires integration of medical findings with psychosocial, contextual, and investigative information. A multidisciplinary approach, involving pediatricians, radiologists, ophthalmologists, and forensic experts, is essential to support accurate medico-legal evaluation and timely protective interventions.